La infografía como recurso de comprensión de datos de los estudiantes de la Escuela Homero Villamil año 2020 - Zamora Tejena, Cristhian Jose (2021)
The investigative work considered as a written dimension of the complex undergraduate exam includes the topic "Infographics as a resource for understanding data from the students of the "Homero Villamil "school year 2020" explaining topics such as the types of infographics, and how to develop it in the educational area, reaching the understanding of its advantages. The investigative study consists of a scheme classified into two chapters describing the methodological framework with the topic of interest, approach to the population problem to be applied to the project, explaining why it was considered to carry out this case in the justification, the objectives that were set for the process of the investigation. The findings found in the research that cannot be written in detail are mentioned when having a data collection instrument that only covers closed questions, therefore any type of manifestation or comment is found in that phase. Possible solutions were set to benefit teachers and students of the institution. As part of these solutions, there are also strategies outlined in the recommendations, ending with the conclusions of the study carried out.